Предмет: Математика,
автор: natashaphanda
Решите уравнение -4 (5-2m) + 3 (m - 4) = 6 (2- m) -5m
Ответы
Автор ответа:
3
-4 (5-2m) + 3 (m - 4) = 6 (2- m) -5m
-20+8m+3m-12=12-6m-5m
8m+3m+6m+5m=12+20+12
22m=44
m=2
Автор ответа:
2
Это оэришение этой задачы
Приложения:
![](https://files.topotvet.com/i/608/608a2b6f27845e9d73313586812e2eba.jpg)
Похожие вопросы
Предмет: Математика,
автор: kalitaulana
Предмет: История,
автор: cherkes00
Предмет: История,
автор: akkfrifaer180
Предмет: Математика,
автор: minas1
Предмет: Геометрия,
автор: ggnoobs